Socialization and Extension of Green Economy to PKK Group and Farmer Groups - Patonah, Siti; Ma'mun, Hisyam; Subekti, Ervina Eka; Supriyanto, Eka Adi (Universitas Lambung Mangkurat, 2025)
Protecting the environment and ensuring its sustainability for future generations are sustainable development goals (SDGs). A preserved environment and ensuring sustainability for future generations is a sustainable development goal (SDGs). Every human activity produces waste that, if not appropriately managed, can bring problems in the future. Before starting a production process that utilizes natural resources, a complete understanding of the